Metode Filsafat Ilmu dan Penerapanya dalam Kajian Manajemen Pendidikan Islam - Oies Febria Siskawati; Rusmita Rusmita; Ardimen Ardimen (Departement of Mathematics Education, 2024)
The philosophy of science plays an important role in the management of Islamic education. It provides a framework for understanding and applying knowledge in educational institutions. This journal will explore the philosophy of science method and its application in Islamic education management. This journal will also discuss various perspectives, analyze positive and negative aspects, and consider possible future developments related to this topic. The research method applied to analyze this issue is the literature review method. Using this method, analysis is carried out on the concepts and theories applied based on available library and reference materials